Induced Seismicity Reduces Seismic Hazard?. Issue 8 (24th April 2019) - Barbour, Andrew J.; Pollitz, Fred
Abstract: Earthquakes caused by human activities have been observed for decades. Often these are related to industrial activities pumping fluids into deep geologic formations, like with wastewater disposal. The simplest theory connecting these processes to earthquakes is straightforward: injection leads to fluid pressure changes that either reduce the strength of preexisting faults or generate new faults. In practice, the conditions that lead to induced earthquakes are not always clear in ways that can be generalized. Kao et al. (2018, https://doi.org/10.1029/2018GL079288 ) show how the distribution of induced earthquakes in Western Canada relate to natural rates of deformation in the crust. Using these new results, they discuss an intriguing paradox: induced seismicity can cause short‐term increases in the seismic hazard that are followed by a period of reduced seismic hazard. Such hazard‐reducing scenarios are plausible but hinge upon simplifying assumptions about how the crust stores and releases strain energy in the form of earthquakes. Key Points: Geodetic data indicate a close relationship between crustal strain rates and induced earthquakes Induced earthquakes might reduce the seismic hazard in the long run Hazard‐reducing scenarios hinge critically on a few major assumptions